2014
DOI: 10.1111/joor.12250
|View full text |Cite
|
Sign up to set email alerts
|

The unique contribution of elements of smile aesthetics to psychosocial well‐being

Abstract: Pleasant smile aesthetics is an important contributory factor to psychosocial well-being. The aim of this study was to determine the psychosocial influence of smile aesthetics. The study was cross-sectional on a convenient sample that included patients, pupils, students and faculty staff. A total of 155 subjects (36% male) aged 12-39 (mean age 21, interquartile range 19-23) were included. Occlusal characteristics were recorded by the Index of Complexity, Outcome and Need, and smiling frontal view photographs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 23 publications
4
38
1
11
Order By: Relevance
“…22 Our previous research confirmed that malocclusions result in higher psychosocial impact than do the parameters of mini-and microesthetics of the smile. 23 Incisor inclinations also have a psychosocial effect, mostly in Class III and Class II division 1 subjects. 24 Excessive anterior tooth display and gingival display during smiling may result in a psychosocial effect of malocclusion, mostly on esthetic concern and least on self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…22 Our previous research confirmed that malocclusions result in higher psychosocial impact than do the parameters of mini-and microesthetics of the smile. 23 Incisor inclinations also have a psychosocial effect, mostly in Class III and Class II division 1 subjects. 24 Excessive anterior tooth display and gingival display during smiling may result in a psychosocial effect of malocclusion, mostly on esthetic concern and least on self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its impact on the psychosocial wellbeing, a positive facial appearance and attractive smile increase the confidence and self-esteem. 1 The orthodontic treatment objective is to correct the malocclusion which might affect the facial and dental esthetics. However, the success of the process might need a positive behavior and cooperation of the patient and treating orthodontist.…”
Section: Introductionmentioning
confidence: 99%
“…Medijski stereotipi važni su u stvaranju nezadovoljstva samim sobom; nakon uspoređivanja vlastita lica i tijela s idealima prezentiranima u medijima ljudi postaju vrlo samokritični i posramljeni zbog svojeg izgleda (11 -13). Snaga reklamiranja potvrđena je činjenicom da najveći promotori oralnoga zdravlja i estetike osmijeha nisu ni stomatolozi, ni preventivne kampanje koje potiče država, nego su to reklame proizvođača sredstava za održavanje oralne higijene (14).Karakteristike osmijeha važan su dio dentofacijalne estetike i sastoje se od njegove širine, vidljivosti, izgleda i položaja zuba, te vidljivost gingive i bukalnih koridora (15,16). Bukalni koridor prostor je koji se pojavljuje tijekom osmjehivanja između bukalnih površina stražnjih zuba maksile i unutarnje stijenke sluznice usnice (17).…”
unclassified
“…The power of marketing is verified by the fact that the biggest promotors of the oral health and smile esthetics are not dentists nor are preventive campaigns run by the state authorities. Instead, they are run by oral hygiene remedies' suppliers (14).Smile characteristics are important features of dentofacial esthetics and are composed of: smile width, visibility, appearance and position of the teeth, visibility of gingiva and buccal corridors (15,16). The buccal corridor is the space that appears during smiling between the labial surface of maxillary posterior teeth and the inner mucosa of the lip (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation